IMAGES OF WAR: THE CONTRA AND THE NICARAGUAN CONFLICT AND IN COSTA RICAN PHOTOJOURNALISM IN THE EIGHTIES - Fernández Morera , Esteban (2025)
This research examines how Costa Rican visual culture represented and visualized the conflict between the Sandinistas and the Contras during the 1980s, through the analysis of war images, specifically journalistic photographs. In this way, it analyzes how these representations, through their emphases and absences, visually reconstructed the conflict and influenced public perceptions of Costa Rican society. For this purpose, the concept of framing is used to analyze the interpretive and propagandistic orientations that journalistic images sought to generate. The study focuses on print media such as La Nación and La República, identified by their warmongering tendency in the context of the Nicaraguan conflict. The article is structured into four sections: first, a theoretical approach to the key concepts of framing and journalistic images; second, the visual coverage of the early stages of the conflict and the figure of Edén Pastora; third, the visual construction of the image of the Contras; and finally, the impact of the La Penca bombing on the local decline of these images. The research argues that visual images constituted a political and cultural battleground in the dispute over the positioning between Sandinistas and Contras in Costa Rica.